2020
DOI: 10.7759/cureus.6780
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polymorphisms in the Promoter Region of NOS2A Gene with Primary Knee Osteoarthritis in the Greek Population

Abstract: IntroductionA new emerging role of nitric oxide (NO) in the aetiology of osteoarthritis (OA) has been reported. Inducible NO synthase (iNOS), produced by chondrocytes, is the major source of NO in the osteoarthritic cartilage. The aim of this study is to evaluate the potential association between the -1173C/T (rs9282799), -1026 C/A (rs 2779249) and -954G/C (rs1800482) single nucleotide polymorphisms (SNPs) in the promoter of the iNOS gene (NOS2A) and the incidence of knee OA in Greek population. MethodsNinety-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…NO and iNOS are important regulators of OA, synovial inflammation, and chondrocyte apoptosis in synovial joint tissues (Leonidou et al, 2020 ). To confirm whether pretreatment with PBSL inhibits the generation of NO and/or iNOS, we measured the levels of NO and expression of iNOS in LPS‐induced RAW264.7 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NO and iNOS are important regulators of OA, synovial inflammation, and chondrocyte apoptosis in synovial joint tissues (Leonidou et al, 2020 ). To confirm whether pretreatment with PBSL inhibits the generation of NO and/or iNOS, we measured the levels of NO and expression of iNOS in LPS‐induced RAW264.7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, cotreatment with various concentrations of PBSL and IL-1β (20 ng/mL) did not result in synergetic toxicity (Figure 3b). (Leonidou et al, 2020). To confirm whether pretreatment with PBSL inhibits the generation of NO and/or iNOS, we measured the levels of NO and expression of iNOS in LPS-induced RAW264.7 cells.…”
Section: Pretreatment Of Pbsl Affected the Expression Of Mmps And The...mentioning
confidence: 99%
“…Unlike synoviocytes, chondrocytes have the ability to self-produce NO, as evidenced by increased levels of iNOS and NO in articular cartilage tissues. However, chondrocytes from patients without OA do not express iNOS, and experimental OA does not develop in iNOS knockout mice [ 130 ]. Some experiments have shown that NO by itself is not cytotoxic to cultured chondrocytes.…”
Section: Molecular Mechanisms Of Gasotransmitter-dependent Apoptosis ...mentioning
confidence: 99%